Modelling of Photovoltaic Module Using Matlab Simulink - Nurul Afiqah , Zainal; Ajisman, Apen; A. R., Yusoff (IOP Publishing, 2016)
Photovoltaic (PV) module consists of numbers of photovoltaic cells that are connected in series and parallel used to generate electricity from solar energy. The characteristics of PV module are different based on the model and environment factors. In this paper, simulation of photovoltaic module using Matlab Simulink approach is presented. The method is used to determine the characteristics of PV module in various conditions especially in different level of irradiations and temperature. By having different values of irradiations and temperature, the results showed the output power, voltage and current of PV module can be determined. In addition, all results from Matlab Simulink are verified with theoretical calculation. This proposed model helps in better understanding of PV module characteristics in various environment conditions.